Sosialisasi Perkoperasian bagi Notaris Pembuat Akta Koperasi Provinsi Jawa Barat dalam Peningkatan Pemahaman Tentang Perkoperasian - Yuanita Indriani (LPPM Universitas Koperasi Indonesia, 2023)
Cooperatives as one of the economic actors in Indonesia are required to be able to compete with other economic actors. Therefore, as a business entity, cooperatives need to obtain certainty and equal legal standing with other economic actors. In this case, the establishment and drawing up of a cooperative deed is carried out by a Notary, as with the establishment of other legal entities. TheDecree of the State Minister for Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 98 of 2004, confirms that a Notary is an official who has the authority to make deeds of establishment and other deeds related either directly or indirectly to cooperative organizational and business activities. To increase the effectiveness of increasing the competitiveness of cooperatives through the availability of legal standing’ Cooperatives are the same as other business actors, so the Notary who makes cooperative deeds needs to understand the characteristics of cooperative organizations as a socio-economic system and is also required to become a community economic movement. An understanding of the characteristics of the cooperative organization is used as the basis or basis for notaries to make the deed of establishment of cooperatives, however, when making the deed of establishment of cooperatives or other deeds related to cooperatives, the deed maker must have a good understanding of cooperatives because the deed made will have legal force and must be legally accountable. For this reason, a cooperative socialization program was implemented for Notaries who make Cooperative Deeds.